Exploring the Effectiveness of Drama-based Learning (DBL) in Elementary Education: Students’ Perceptions and Subject Preferences - Panda, Raj Ballav; Sahu, Ghanashyam; Singh, Meenakshi; Mahakur, Binod (Voices of Teachers and Teacher Educators, 2024)
The National Education Policy (NEP) 2020 emphasises the importance of 21st-century skills and interactive teaching methods. This study investigated elementary-level students’ perception of drama-based teaching and explored any potential differences between male and female students. A descriptive survey method was employed, in which 50 students were taught using drama. The findings suggest that drama-based learning (DBL) is both effective and engaging, especially for language-based subjects, as it promotes exploration, discovery, and problem-solving skills. There was no significant difference in perception between boys and girls, although language subjects were preferred over Mathematics, Science/EVS, and Social Science. This study highlights the potential of DBL as an effective tool for holistic development in elementary education.